ECONOMIC ANALYSIS AND WATERS QUALITY SEAWEED FARMING (Eucheuma cottonii) IN THE DISTRICT OF BANGKEP - Saharia Kassa; Bakri Hasanuddin; Madinawati Madinawati (Tadulako University, 2016)
Seaweed farming development received support from local government with “Gema Biru Sulawesi Tengah” which makes seaweed commodities became the competitive commodity across sectors in the region. Nowadays, the demand of the dried seaweeds as well as semi-finished products (semi-finished carrageenan) tends to be increased rapidly because they are classified as healthy food. On the other hand, the farmer in the district of Bangkep relatively still being traditional by planting in the territorial which estimated suitable for seaweed. The Study aims to identify the water potential of seaweed farming and to analyze the economic variables that affecting the production of seaweed based on its deployment area. This research is conducted in Bangkep in 4sub-districts area i.e. Bulagisub-district (Peling Peasa, Bulagi and Kambal village), South Bulagi District (Bulagi, Palabatu, and Lolantang village), South Tingkung district (Tinangkung, Bobu and Gangsal village) and Liang district (Apal, binatuli and Liang village). The determination of locations is done purposively with 56 respondents. The data Analysis used are suitability analysis with water measurement and testing of water sample as well as regression analysis. The research shows that the locations of the farms have water quality which suitable with the seaweed, which shown by the result of the physical-chemical measurement parameters that meet with the growing requirements in the range of achievement 74.00-82.67%. Economic aspects show the average income of the seaweed farmers are Rp. 1.614.434. Further variables simultaneously independent (age, education, number of dependents, experience, the amount of expanses, and prices) that affect the production of seaweed, while partially only age, experience, amount of expanses, and prices significantly affect the production on the t value of each are 2.57; 3.69; 2.49; and 2.33.